High Prevalence of Vitamin D Deficiency in Patients with Bone Tumors. (14th September 2017) - Horas, Konstantin; Maier, Gerrit; Jakob, Franz; Maus, Uwe; Kurth, Andreas; Jakuscheit, Axel; Rudert, Maximilian; Holzapfel, Boris Michael
ABSTRACT: The aim of this study was to evaluate the prevalence of vitamin D deficiency in patients with different types of bone tumors and to elucidate whether or not there are differences in prediagnostic vitamin D levels in patients with malignant compared to benign bone tumors. Prediagnostic serum 25(OH)D levels of 105 consecutive patients that presented with bone tumors and tumor-like lesions to two Orthopedic Level I University Centers in Germany between 2011 and 2016 were measured on admission. We found an alarming and widespread rate of vitamin D deficiency in patients with bone tumors. Specifically, 83% of all patients had low vitamin D levels with a mean 25(OH)D level of 19.82 ng/ml. Notably, patients diagnosed with malignant bone tumors had significantly lower vitamin D levels compared to patients with benign bone lesions ( p = 0.0008). In conclusion, it is essential to assess vitamin D levels in patients with tumors involving bone. In addition, there might be an association between vitamin D deficiency and the onset or course of primary malignant bone tumors.